Peningkatan Budaya Literasi Konsumen atas Label Pangan Kemasan dan Obat-Obatan - Anggraini, Anna Maria Tri; Abrianti, Sharda; Bachry, Ramadhana Anindyajati (Empowerment, 2023)
The labeling of processed food and medicines is needed as an effort to fulfill consumers' rights related with correct, clear and honest information in accordance with Article 4 of Law No. 8/1999 concerning Consumer Protection (UUPK). However, in practice it is not easy for Micro Small and Medium Enterprise (MSME) business actors to fulfill production requirements considering the level of understanding and the cost of labeling. Therefore, it is necessary to know the form of consumer protection for processed food and medicines, especially for MSME business actors in the novice business community; and increasing the literacy culture among the community regarding processed food and medicine labels, particularly in Kebon Jeruk area, West Jakarta. Implementation of Community Service activities is carried out online through zoom meeting using counseling techniques. This theme is intended to provide education to novice MSME businessmen so that manufacturers of processed food and medicines carry out their obligations in accordance with regulatory provisions and policies of the relevant authorities. The target subject of this activity is carried out in the Kebon Jeruk area, West Jakarta, by involving the head partner of the local MSME entrepreneur association which is generally engaged in the processed food business. Counseling participants were so enthusiastic about the theme given considering that this information had never been conveyed to business actors or the public. Disseminating information on labeling obligations on food products is the duty and function of the food authority and all stakeholders in consumer protection. It requires the involvement of all parties, including the government, business actors, and observers of consumer protection to increase further understanding regarding clear, correct and honest labeling. In this way, it is hoped that it can improve the community's literacy culture towards achieving the consumer empowerment index at a more critical level.Pelabelan pangan olahan dan obat-obatan diperlukan sebagai upaya pemenuhan hak konsumen atas informasi yang benar, jelas, dan jujur sesuai Pasal 4 UU No. 8/1999 tentang Perlindungan Konsumen (UUPK). Namun pada praktiknya tidak mudah bagi pelaku usaha UMKM untuk memenuhi persyaratan produksi mengingat tingkat pemahaman dan biaya pencantuman label. Karenanya perlu diketahui bentuk perlindungan konsumen pangan olahan dan obat-obatan khususnya bagi pelaku usaha UMKM pada komunitas pebisnis pemula; dan peningkatan budaya lliterasi bagi masyarakat terkait label pangan olahan dan obat-obatan khususnya di wilayah Kebon Jeruk Jakarta Barat. Pelaksanaan kegiatan Pengabdian kepada Masyarakat dilakukan secara daring melalui media zoom meeting dengan menggunakan teknik penyuluhan. Tema ini dimaksud untuk memberikan edukasi kepada pebisnis pemula UMKM agar produsen pangan olahan dan obat-obatan melaksanakan kewajibannya sesuai ketentuan regulasi dan kebijakan otoritas terkait. Sasaran subyek kegiatan ini dilaksanakan di daerah Kebon Jeruk Jakarta Barat dengan melibatkan mitra ketua asosiasi pengusaha UMKM setempat yang pada umumnya bergerak di bisnis pangan olahan. Peserta penyuluhan sangat antusias dengan tema yang diberikan mengingat informasi tentang hal ini belum pernah disampaikan kepada pelaku usaha maupun masyarakat. Penyebarluasan informasi kewajiban pelabelan pada produk pangan merupakan tugas dan fungsi otoritas pangan dan semua pihak pemangku kepentingan perlindungan konsumen. Perlu keterlibatan semua pihak, baik pemerintah, pelaku usaha, dan pemerhati perlindungan konsumen untuk meningkatkan pemahaman lebih jauh terkait pelabelan yang jelas, benar dan jujur. Dengan demikian diharapkan dapat meningkatkan budaya literasi masyarakat menuju pencapaian indeks keberdayaan konsumen ke tingkat lebih kritis.